“Argue With Me”: A Method for Developing Argument Skills - Iordanou, Kalypso; Rapanta, Chrysi (Frontiers in Psychology, 2021)
Philosophers, psychologists, and educators, all acknowledge the need to support individuals to develop argument skills. Less clear is how to do so. Here we examine a particular program, the “Argue with Me” dialog-based pedagogical approach, having this objective. Reviewing approximately 30 studies that have used the “Argue with Me” (AWM) method, with students of different backgrounds and educational levels – primary, middle, high school and university – across 5 different countries, we examine its strengths and limitations in terms of what develops and how this development occurs. Dense engagement in goal-based activities involving extended dialogic practice and reflection is shown to be effective in fostering argument skills and dispositions. Studies examining the mechanisms of such development identify the role of meta-level understanding regarding the purpose of argument. This understanding is epistemological in nature and supports development of dialogic skills at the strategic level. In addition to examining the AWM method as a means for supporting the development of argument skills, this review examines how empirical research employing the method in varying contexts provides insights into the nature of argument skills and their development, as well as relations between argument skills and other skills or forms of understanding. For instance, we examine how studies employing the AWM method answer questions such as “How general or content-specific are argument skills?” or “How do dialogic argument and individual written or spoken argument connect as they develop?” We address these questions by examining evidence regarding the transfer of gains across topics, domains, and individual vs. dialogic modes of expression. Finally, the pedagogical implications of the “Argue with Me” approach are discussed, especially with regard to its potential both as a stand-alone method for developing argument skills and integrated into traditional literacy and social studies curricula.